Influence of continuous erythropoietin receptor activator (CERA) administration intervals on erythropoietic effect in hemodialysis patients. Issue 1 (December 2016) - Daimon, Shoichiro; Nuka, Hiromi; Kitada, Kinya; Suzuki, Yasunori; Kim, Fae; Kawano, Mitsuhiro
Abstract Background Erythropoietin deficiency is the major cause of anemia in hemodialysis patients. Although continuous erythropoietin receptor activator (CERA) has a long half-life and once-monthly administration is recommended, the optimal interval to achieve the greatest efficacy is not known. Methods In 44 hemodialysis patients, CERA was administered at an interval of once every 2 weeks (Q2W) and 4 weeks (Q4W) consecutively and reticulocyte counts and hemoglobin levels were compared prospectively. In six patients with CERA 100 μg/4 weeks, CERA intervals were further changed to 1 week (Q1W). Results Mean reticulocyte counts were higher during Q2W than Q4W (41.5 ± 10.7 and 36.4 ± 8.8 × 103 /μL, respectively, p < 0.0001), and hemoglobin levels decreased during Q4W. These results were irrespective of the CERA dose (50, 100, and 150 μg/4 weeks). In six patients with CERA 100 μg/4 weeks, although not significant, reticulocyte counts were higher during Q2W and Q1W than Q4W and hemoglobin levels were highest during Q1W (p < 0.05). Conclusions In our hemodialysis patients, an interval of CERA shorter than 4 weeks appeared to be more effective for the treatment of anemia.